(3QSGdI aj GdBOGH dcahjs - (3Gdcahj, eMeO Hf MejO Hf eUWai, (B1174 (3g`s
(3ChdgG (B:s
(3MeOG ddg Ydi fYeGFg (B... (3gPg QSGdI aj GdBOGH dNUJgG ef cJH gPG GdHGH JMaI dHYV GdCMHGH hJPcQG dGhdj GdCdHGH GYde Gfc EPG bdJ HcdGe adc NeSI MGdGJ MGdI GdOYhi s
(3BNQgG (B:s
(3g GdhLhg aEeG Cf JLO TjFG jOaY ChdG JLO TjFG CUdG aPc CeG GdceGd ef MQQg hHjfg Ch dbUQc adG JaJQ LOc aGfXQ aj GdHMK GdKGfj CjVG Ydi hLg GdSGHb Ke aj GdKGdKs
(3QHeG Jchf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\270s
(3EjVGM Gdecfhf (B1\3s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdadSaI hGdefWbs